2019
DOI: 10.1039/c9tc01822k
|View full text |Cite
|
Sign up to set email alerts
|

Developing photocathode materials for p-type dye-sensitized solar cells

Abstract: Dye-sensitized solar cells are photoelectrochemical devices, which are of great interest due to their ease of fabrication and attractive design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 217 publications
1
59
0
Order By: Relevance
“…It has also recently been exploited to develop artificial photosynthesis devices for low-cost CO 2 -free hydrogen photo production 24 . Recent progress in the development of more efficient dye-sensitized solar cells and dyesensitized photocathodes is reported in review articles 25,26 . The electronic properties of an organic layer can be drastically modified by the local arrangement of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It has also recently been exploited to develop artificial photosynthesis devices for low-cost CO 2 -free hydrogen photo production 24 . Recent progress in the development of more efficient dye-sensitized solar cells and dyesensitized photocathodes is reported in review articles 25,26 . The electronic properties of an organic layer can be drastically modified by the local arrangement of the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…While this perspective focuses on the semiconductor materials, it should be noted that there are multiple ways to improve the efficiency, and focusing on the individual components as well as their interaction is significant to move forward. Advances in the dyes, [21][22][23][24][25][26] electrolytes 19,21,[27][28][29] or in general 17,21 can be found in the literature.…”
Section: Dye-sensitised Solar Harvesting Devicesmentioning
confidence: 99%
“…Due to its large band gap of 3.6-4.0 eV, 38 NiO exhibits good transparency for thin films, despite the underlying brown colour due to Ni 3+ ions that are present as a result of Ni 2+ vacancies that form during sintering. 21 In an investigation of a range of different mesoporous NiO electrodes prepared by different research groups, Gibson et al 39 could show that the performance of NiO depends on not only the crystallite size and film thickness but also on sintering temperature, all of which influence the crystallinity and surface states. Furthermore, Hammarström et al 40 found out that these surface states are involved in hole trapping and act as tunnelling sites on a sub-ps timescale which lead to rapid recombination with the redox mediator.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations